Bacteriophage Growth Promoters in Poultry - C. Honorio Javes; Y. Vallenas Sánchez (ESPOCH Congresses, 2021)
Abstract In recent years, there has been an increase in bacterial resistance to antimicrobials found in both animals and humans, and in some countries, the use of antibiotics as growth promoters has been prohibited. Therefore, this article reviewed bacteriophages (viruses that infect bacteria) as a substitute for antibiotic-type growth promoters, since they can help control the main bacterial pathogens such as Salmonella and E. coli that affect birds, improve production parameters in broilers and laying hens, and are more efficient than antibiotic-type growth promoters.